VERBA BERVALENSI DUA PADA BAHASA MADURA DALAM FILM PENDEK REJEKI SUDAH DIATUR (KAJIAN SINTAKSIS) - Moh. Tarojjil Mahbub; Dwi Suryani; Haris Khoironi; Sumarlam (Jurnal Bastra (Bahasa dan Sastra), 2024)
This research aims to describe double-valent verbs in Madurese language compound and simple sentences in the short film "Rejeki Sudah Diatur". This research uses a syntactic approach with qualitative descriptive methods. The data in this research is in the form of conversations between characters in the short film in which there are double-valent verbs and their context. The data source in this research is a short video film with the title "Rejeki Sudah Diatur" which was uploaded on the Mavia Project YouTube channel and has a duration of 18:21. The data collection method in this research uses the listening method and advanced techniques of proficient free-involved listening, as well as note-taking techniques through orthographic transcription. The analytical method used is the ethnographic method with the Spradley model covering domain analysis, taxonomy analysis and componential analysis by eliminating cultural theme analysis. In this study, 6 data were found, in the form of sentences that had the structure SPOP1 and included verbs with two valences.